The Late Neoproterozoic-Early Paleozoic basin of the western Argentine Precordillera: Insights from zircon U-Pb geochronology. (October 2020) - Boedo, F.L.; Pérez Luján, S.; Naipauer, M.; Vujovich, G.I.; Pimentel, M.M.; Ariza, J.P.; Barredo, S.P.
Abstract: In central-western Argentina, a belt including marine metasedimentary rocks and mafic-ultramafic bodies occurs throughout the western margin of the Precordillera. The belt is considered as the suture zone between the poorly known Chilenia terrane and the Cuyania terrane, part of the composite West Gondwana margin. It is assigned to the Late Neoproterozoic-Early Devonian based on fossil fauna and radiometric ages. In the southern sector of this belt, in the Peñasco area, two units crop out. The Peñasco Formation comprises metasandstone and metapelite spatially associated with mafic metavolcanic and metahyaloclastic rocks. Metagabbro bodies intrude the succession. The Garganta del León Formation consists of metasandstone and scarce metapelite where tractive and deformational sedimentary structures are preserved. Both units are affected by low-grade metamorphism, but the main foliation S1 and crenulation cleavage S2 are better developed in the Peñasco Formation rocks. U-Pb data on detrital zircon of two metasandstone samples from these units show a dominant detrital input from sources with 1.0–1.3 and 0.65–0.53 Ga ages. Detritus may come from reworked sedimentary units or from igneous/metamorphic complexes from the Cuyania terrane basement that was possibly exhumed in the Ocloyic orogen. A Gondwanan provenance for the Late Neoproterozoic-Cambrian population would also be plausible. A ca . 460 Ma zircon population in the Garganta del León Formation is interpreted to be derived from the Famatinian Arc. This would imply that the deposition of the sediment occurred after the collision of the Cuyania terrane against West Gondwana, and that the Ocloyic orogen acted as a barrier for detritus from the Famatinian Arc and other rocks further east. Highlights: Two stratigraphic units are redefined: the Peñasco and Garganta del León formations. Detrital zircon dating constrains source rock ages to the Meso- and Neoproterozoic. The Ocloyic orogen acted as source and as a barrier for detrital input from Gondwana. Cuyania accreted to Gondwana before the deposition of the Garganta del León Formation. The Famatinian arc provided detritus to the western Cuyania marine basin.